Pertolongan Pertama pada Luka Kena Pisau - Anggi Putri Utami; Hasima Harahap; Rahma Fadillah Siregar; Usiono Usiono (Journal of Educational Innovation and Public Health, 2024)
The incidence of injuries is increasing every year, both acute wounds and chronic wounds. A recent study in America showed that the prevalence of patients with wounds was 3.50 per 1000 population. The majority of wounds in the world's population are wounds due to surgery/trauma (48.00%), foot ulcers (28.00%), decubitus wounds (21.00%). In 2009, MedMarket Diligence, a wound association in America conducted research on the incidence of wounds in the world based on disease etiology. Data obtained for surgical wounds were 110.30 million cases, trauma wounds 1.60 million cases, abrasions there were 20.40 million cases, burns 10 million cases, decubitus ulcers 8.50 million cases, venous ulcers 12.50 million cases, diabetic ulcers 13.50 million cases, amputations 0.20 million per year, carcinoma 0.60 million per year, melanoma 0.10 million, skin cancer complications there are 0.10 million cases. Injuries that occur in all our daily activities. Abrasions due to falls, injuries from sharp objects such as knives, nails and so on are considered minor injuries.